Development and implementation of a seismic characterization and CO2 monitoring program for the Illinois Basin – Decatur Project. Issue 5 (October 2014) - Couëslan, Marcia L.; Smith, Valerie; El‐Kaseeh, George; Gilbert, John; Preece, Nikolas; Zhang, Lei; Gulati, Jitendra; Greenberg, Sallie
Abstract The Illinois Basin – Decatur Project (IBDP) is a carbon capture and storage (CCS) project that is located at the Archer Daniels Midland (ADM) Company's corn processing plant in Decatur, Illinois. The IBDP has an extensive seismic program that was designed to meet site characterization and monitoring objectives that includes two‐dimensional (2D) and three‐dimensional (3D) surface seismic data, time‐lapse 3D vertical seismic profiles (VSPs), and microseismic monitoring. As little deep subsurface data was available within a 20‐mile (32‐km) radius of site, the surface seismic surveys have been important to the site characterization objectives for the project. Through seismic inversion analysis, rock properties such as density, porosity, and rock lithology were derived from the surface seismic data and incorporated into the geologic and geomechanical models for the project. Time‐lapse 3D VSPs are acquired with a permanent geophone array in Geophysical Monitoring Well #1 (GM1). Carbon dioxide (CO2) injection commenced in November 2012, and the first monitor survey was acquired in February 2012 after approximately 70 000 tonnes of CO2 had been injected. While this is a small volume of CO2 to detect seismically, anomalies were identified that may be suggestive of CO2 movement in the Mt Simon Sandstone at the depth of injection. Microseismic activity has been monitored using the geophone array in GM1 and two deep geophones installed in the Injection well (CCS1). A comparison of the different operation parameters with microseismic activity shows a correlation between microseismicity and pressure changes in the formation.